Conductive-perovskite LaNiO3 Thin Films Prepared by Using Solution Process for Electrode Application - Nguyen, Quang Hoa (H. : ĐHQGHN, 2018)
Lanthanum nickel oxide LaNiO3 (LNO) isextensively known as one of typical perovskite-structured materials with metallic conductivity, which is suitable for the electrode application in electronic devices such as transistors or solar cells. Since LNO is a low-cost material and a simple fabrication process, it has been attracted much attention for commercialization. In this paper, we have focused on optimizing the fabrication process of LNO thin films on SiO2/Sisubstrate and Al foil by using asolution process. The crystal structure and surface morphology were characterized by using X-ray diffraction and field-emission scanning electron microscopy (FE-SEM), respectively. It was found that the LNO thin films annealed in range of 550-700oC for 30 minutes exhibited a well-formed crystallization and a dense microstructure. According to the SEM cross-sectional observation, the thickness of LNO thin films was estimated about 80 nm. Also, from the four-probe measurement method, the electrical resistivity of LNO thin film annealed at 600oC had a minimum value of 0.42× 10-2 Ωcm, which waspossibly comparable to conventional conductive oxides. As a result, thecapacitor using Pb1.2(Zr0.4Ti0.6)O3ferroelectric layer annealed at 600oC and LNO bottom electrode providedan interesting ferroelectricity, which includeda remnant polarization of 21µC/cm2 and a saturated polarization of 35µC/cm2 . Moreover, the leakage current density was lower than 2 × 10-5 A/cm2 .